Human pericardial extracellular matrix: An implantation platform for cardiac tissue engineering - Castells-Sala, Cristina; Prat-Vidal, Cristina; Roura, Santiago; López-Chicón, Patrícia; Fariñas, Óscar; Bayes-Genis, Antoni; Rodríguez-Gómez, Luciano; Vilarrodona, Anna (Frontiers in Biomaterials Science, 2022)
Tissue engineering, which involves the use of therapeutic biologicals supported by implantable materials, represents a promising tool to repair damaged tissues or organs. Among the most proper supporting materials and scaffolds, natural extracellular matrix (ECM) constitutes a dynamic platform of structural and functional fibers and biomolecules that confers a suitable microenvironment for cell attachment, proliferation and differentiation via activation of host signaling cues. In this context, ECM derived from human pericardium emerges as a supportive porous biomaterial to regenerate post-infarcted myocardium. In specific, pericardial ECM highlights as a potential clinical option for administering those active components grown and purified from large-scale cell cultures, such as mesenchymal stromal cells and derived extracellular vesicles, and to locally generate a vascularized bioactive niche promoting modulation of post-ischemic inflammation and cardiac repair.